The Role of the Vascular Endothelial Growth Factor (VEGF) Signaling in Biomineralization of the Oyster Crassostrea gigas - Ivanina, Anna V.; Borah, Ballav; Rimkevicius, Tadas; Macrander, Jason; Piontkivska, Helen; Sokolova, Inna M.; Beniash, Elia (Frontiers in Marine Science, 2018)
Vascular endothelial growth factor (VEGF) and vascular endothelial growth factor receptor (VEGFR) play a role in early development, organogenesis, and regeneration, as well as biomineralization of invertebrates. The involvement of VEGF and VEGFR in biomineralization was demonstrated in sea urchin larvae but its role in the biomineralization of other invertebrate groups such as mollusks is not known. We assessed the potential role of VEGF signaling on biomineralization of a model marine bivalve, the Pacific oyster Crassostrea gigas, by analyzing the effects of a VEGFR inhibitor (50 nM axitinib) on shell growth, shell hardness, and expression profiles of biomineralization-related genes. Bioinformatics analysis identified a wide range of biomineralization-related genes potentially activated by VEGF including carbonic anhydrases (CAs), sodium/proton and sodium/calcium exchangers, calmodulins, and genes involved in chitin metabolism. Exposure to a VEGFR inhibitor axitinib led to upregulation of CAs (CA7 and CA12), sodium/proton exchanger 10, sodium/calcium exchanger 1 and 3, as well as calmodulin mRNA in hemocytes (HCs). In the mantle tissue, axitinib exposure led to a compensatory upregulation of VEGFR mRNA but did not affect the expression of other studied biomineralization genes. Expression of VEGF, VEGFR mRNA, or that of the downstream biomineralization-related genes in a non-biomineralizing tissue (the gill) was not affected by axitinib. The shell mass was higher in the axitinib treatment group. Inhibition of VEGFR led to significant increase in shell microhardness, and to a small but statistically significant decrease in crystallinity. Our results therefore indicate that, although VEGF signaling might not play a crucial role in shell biomineralization of C. gigas as it does in mammals and echinoderms, it is involved in regulation of shell formation in bivalves and that effects of VEGF on biomineralization are likely mediated by HCs.